2014
DOI: 10.5599/jese.2014.0054
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetics and soil decontamination: concepts and overview (Review)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…By using a low-level direct current (DC) electrical potential difference across electrode pairs placed in-ground, contaminants in the soil are moved under the action of the electrical field. The extraction of contaminants by the EK remediation assumed that the metal ion was in the liquid phase on the soil pores [34]. The variation in the amount of remaining silver concentration after EK remediation in the soil cell for each test was shown in Figure 5.…”
Section: Profiles Of Silver (Ag) Concentrationsmentioning
confidence: 99%
“…By using a low-level direct current (DC) electrical potential difference across electrode pairs placed in-ground, contaminants in the soil are moved under the action of the electrical field. The extraction of contaminants by the EK remediation assumed that the metal ion was in the liquid phase on the soil pores [34]. The variation in the amount of remaining silver concentration after EK remediation in the soil cell for each test was shown in Figure 5.…”
Section: Profiles Of Silver (Ag) Concentrationsmentioning
confidence: 99%
“…However, this review stressed on the additional effort that was needed in evaluating the potential limitations in modeling these electrokinetic processes in terms of the assumptions inherent in the models and fieldscale applications. Karim [21] reviewed several other modeling efforts and found that although these studies provide valuable understanding and experience on the modeling of electrokinetic and other similar processes, almost none of them provided any form of analytical solutions as oppose to numerical solutions. Simple particular and trivial analytical solutions of models sometime can provide valuable and close results that can be used in different scenarios.…”
Section: Insights In Analytical Electrochemistrymentioning
confidence: 99%
“…The first documented real life application of EK remediation for removal of salts from alkali soils was reported as early as in the 1930s from India [6]. Several researchers have worked on the use of EK in remediation of contaminated soils [5], [7]- [11]. Karim [11] states that the success of EK in soil remediation and decontamination validates its ability as a cost effective and viable in-situ remediation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have worked on the use of EK in remediation of contaminated soils [5], [7]- [11]. Karim [11] states that the success of EK in soil remediation and decontamination validates its ability as a cost effective and viable in-situ remediation technique. However, the use of EK for soil improvement have been rare and limited to electroosmosis according to Abdullah and Al-Abadi [3].…”
Section: Introductionmentioning
confidence: 99%